Personnel and Human Resource Planning in Educational Institutions - Annaas Khoiri; Suyatman, Suyatman (Penerbit Hellow Pustaka, 2025)
This research aims to provide stimulus in the recruitment of human resources in the world of education. Human resources or teachers who are competent in their fields are very much needed in supporting the vision and mission of institutions or organizations. because in achieving the goals of each activity can run effectively and efficiently, this is very dependent on the good and bad quality of human resources or teachers owned. Therefore, it is important and must be a special view by the organization in taking or recruiting human resources or teachers who are in accordance with the needs and qualifications of the institution. Moreover, in an activity, human resource planning is very important for planning educational institutions in the future. First, human resources are closely related to the planning process chain, because they connect the culture of the institution with humans as a model and its flexibility. Second, during the implementation of the work plan, recruiters must follow a structured model in the form of Estimated labor demand, labor supply, and in-depth recruitment according to needs. Third, teachers can be accepted from several aspects.